DRASTOP BENEFICIAL PROPERTIES FOR THE BODY - Ergashov Bekhruzjon Komilovich (TADQIQOTLAR.UZ, 2024)
Osteoarthritis (OA) is one of the most widespread illnesses in the other half of a person’s life and one of the main reasons for wasting productivity [1]. According to other authors, OA reflects most importantly the characteristic age of the age (30–50 years), with a significant number of episodes (20%) of the first signs being recorded in up to 30 years [2, 3]. Forecasts of the World Health Organization indicate that in the next 10–15 years, OA will become the fourth leading cause of disability in women and the eighth in men [4]. However, the relevance of studying the pathogenesis and treatment of OA is beyond doubt. Researched doses were determined based on the results obtained when studying the acute toxicity of CHF. According to these results, CHF belongs to the class practically non-toxic substances, as in a dose of 1000 mg/kg it did not cause deaths as in the group of mice, as well as in the group of rats. Therefore, we consider a dose of 1000 mg/kg to be maximally tolerated at a single dose inputs (LD0). The results of a study of the effectiveness and tolerability of chondroitin sulfate (Drastop) in the complex treatment of patients with chronic back pain are presented. All patients (n = 50) received standard therapy, including nonsteroidal anti- inflammatory drugs and muscle relaxants.